Is early postnatal growth velocity, a proxy of minipubertal androgen action, related to adult second‐to‐fourth digit (2D:4D) ratios in men? A test in Cebu, Philippines. Issue 6 (31st July 2017) - Georgiev, Alexander V.; Ryan, Calen P.; Borja, Judith B.; Kuzawa, Christopher W.
Abstract: Objectives: The ratio of the length of the second to the fourth digit (2D:4D) of the hand is often used as an index of prenatal androgen exposure but it might also be affected by androgens during "minipuberty, " a period of temporarily high testosterone (T) production in the first few months of life. To examine this, we tested the prediction that men with lower 2D:4D ratios had greater weight growth velocities during the first months of life—a metric recently shown to correlate with concurrent T levels. Methods: We related early growth data to 2D:4D ratios of both hands measured in 756 men (25–26 years) from Cebu, The Philippines. Results: Birth‐to‐fourth‐month (B4M) weight gain velocity (a proxy of early postnatal androgen action) was not associated with adult 2D:4D ratios of either hand, when the latter was measured continuously. When comparing men with more male‐typical digit ratios (<1.0) to those with more female‐typical ratios (≥ 1.0), the group of men with more male‐typical ratios had greater B4M weight velocity, but this was only the case for the left hand. Conclusions: We found modest evidence that adult digit ratios relate to an anthropometric correlate of androgen exposure during minipuberty. Definitive assessment of the role of postnatal T in shaping digit ratios will require direct measures of perinatal T related to longitudinally assessed digit ratios.